Determining factors of the reading habits of the University community: The case of a Chilean State University - Viera Castillo, Daniel Omar (2022)
This research studies the determining factors of reading habits in university students of a Chilean State University. The studies of reading habits in Chilean state universities are not too many, the formation of the reading student, derives in an education for the pleasure of reading, for which, it is intended to study what factors are key at the time of the student's formation. . The study was developed with a bivariate correlation model and a sample of 169 respondents was studied. Determining that the variables the family environment and technology are those that influence the reading habits of the students of the State University studied.